SPERM MORPHOLOGICAL ABNORMALITIES IN ASTHENO OLIGOSPERMIC FRIESWAL BULLS - MANDAL, D K; KUMAR, M; TAYAGI, S; KUMAR, SATISH (The Indian Journal of Animal Reproduction, 2023)
Eighteen mature Frieswal (Holstein Friesian X Sahiwal; having 5/8 exotic inheritance) bu/ls ofsimilar age (29.79±0.90 months) were divided into 2 categories i.e. poor (N=9, sperm motility< 50%and concentration
Keywords: Sperm abnormality; Frieswal Bull; Poor semen quality